Severe Vitamin D deficiency causing kyphoscoliosis - Abhishek Singhai; Subodh Banzal (Journal of Family Medicine and Primary Care, 2013)
Vitamin D deficiency is common among Indian population. Women are especially at risk for severe vitamin D deficiency. The risk is higher for those who are multiparous and postmenopausal. Poor exposure to sunlight, higher latitude, winter season, inadequate diet, older age, obesity and malabsorption are also important risk factors. Symptoms of hypovitaminosis D, including diffuse or migratory pain affecting several sites (especially the shoulder, pelvis, ribcage and lower back) have also been misdiagnosed as musculoskeletal disorders, including fibromyalgia, polymyalgia rheumatica and ankylosing spondylitis. Here, we report two cases presented with kyphoscoliosis, diagnosed to have severe vitamin D deficiency.